Peningkatan Hasil Belajar Pendidikan Pancasila melalui Penerapan Media Inovatif Berbasis Model Pembelajaran Problem Based Learning bagi Siswa Sekolah Dasar Kelas 4 - Elsa Setianing Wahyu; Novita Erliana Sari; Fitriana Novarina (Jurnal Pustaka Cendekia Pendidikan, 2025)
This research aims to apply innovative media based on Problem Based Learning as one of the efforts to help the learning difficulties of class IV students at SD Negeri Putat 01 Madiun Regency. This type of research is classroom action research (PTK). This research used descriptive quantitative research with 3 meetings, namely Pre-Cycle, Cycle I and Cycle II. This data collection technique is observation, interviews and documentation. The results of this research show that learning outcomes increased after implementing innovative media based on Problem Based Learning. In cycle I the average score of students was 72 while in cycle II their average score was 81.There was an increase in student learning outcomes.